DIABETIC KETOACIDOSIS (DKA) AS A RARE PRESENTATION OF PHEOCHROMOCYTOMA - Marzukie, Marisa Masera; Ali, Norhaliza Mohd (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Pheochromocytoma commonly presents with hypertension. Diabetes mellitus is one of the extremely rare metabolic complications of pheochromocytoma and is seen in a third of patients with pheochromocytoma. We present a patient with pheochromocytoma whose initial presentation was DKA. CASE A 39-year-old Indian female presented with abdominal pain and fever and was diagnosed with DKA. Her weight was 40kg with BMI of 17kg/m2. Her blood pressure was 90/60 mmHg. Underlying sepsis was suspected in the presence of leucocytosis (WBC 22x109/L). Abdominal ultrasound showed a solitary liver lesion at segment V/V1. The CECT revealed a well-defined capsulated right suprarenal mass measuring 5.4 x 6.2 x 7.8 cm. Urine epinephrine level was elevated, 117.8 ug/day (0.5-2 ug/day), while both metanephrine and dopamine levels were normal. A diagnosis of right adrenal pheochromocytoma was made. She was lost to follow-up but continued her diabetes management in the primary care clinic and remained on basal-bolus insulin. Four years later, she presented again with right-sided abdominal discomfort, with episodes of headache, palpitations and sweating. She also developed hypertensive crisis during this admission. CECT showed a large heterogeneously enhancing right suprarenal mass measuring 7.7 x 8.1 x 10.4 cm with mass effect to the inferior border of the liver and displacement of the right kidney with no evidence of distant metastasis. Urine metanephrine level was elevated at 82.2umol/day (0-1.62 umol/day) while urine normetanephrine level was 10.0 umol/day (0-2.13 umol/day) She underwent right adrenalectomy. Post-operatively, she was euglycemic and normotensive and was discharged without any antihypertensives and insulin. CONCLUSION Pheochromocytoma rarely presents with DKA. The presence of DM in a young, lean patient might be the clue. Hypertension might not be present in the beginning as in this patient. Close glucose monitoring intra- and postoperatively is important as hypoglycaemia may occur after tumour resection.